Pengaruh Kinerja Keuangan terhadap Corporate Social Responsibility: Studi Empiris pada Sektor Health Care yang Terdaftar di BEI Tahun 2020-2024 - Alifiah, Afsah; Karnawati, Yosevin (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to analyze and provide empirical evidence on the influence of financial performance on corporate social responsibility (CSR) in healthcare companies listed on the Indonesia Stock Exchange (IDX) during 2020-2024. This quantitative research employs a descriptive explanatory causality approach to examine the relationships between variables. The sample consists of 19 companies selected through purposive sampling, resulting in 95 observations. Data were analyzed using multiple linear regression. Classical assumption tests indicate that the data are normally distributed, while initial autocorrelation issues were addressed using the Cochran Orcutt approach, after which no violations of autocorrelation, multicollinearity, or heteroscedasticity were detected. The results show that return on assets (ROA), current ratio (CR), and net profit margin (NPM) simultaneously influence CSR. Partially, ROA has a negative and significant effect, while CR and NPM have positive and significant effects on CSR. This study contributes to legitimacy theory by providing empirical evidence of the role of financial performance in CSR disclosure within the Indonesian healthcare sector, while the negative effect of ROA offers additional insight into going concern theory. Practically, companies are advised to maintain liquidity levels between 150%-300% and optimize profit margins to support CSR strategies, while investors may use financial ratios as indicators to predict CSR performance.